Financial Inclusion Strategies (Exploring The Landscape Through Systematic Literatur Review) - Suprapti, Ida Ayu Putri; Harsono, Iwan; Sutanto, Himawan; Chaidir, Taufiq; Arini, Gusti Ayu (Accounting Studies and Tax Journal (COUNT), 2024)
This research aims to explore financial inclusion strategies through a systematic literature review approach. Using specific keywords in academic databases, this research identifies, filters, and analyzes relevant articles. The research results and discussions highlight key categories, including financial technology, financial literacy, financial infrastructure, policies and regulations, consumer safety, gender equality, cross-sector collaboration, and adaptation to local conditions. This research concludes that a holistic approach that considers these factors is the key to success in achieving effective financial inclusion.